Transit Peptides Often Require Downstream Unstructured Sequence for Efficient Chloroplast Import in Chlamydomonas reinhardtii - Caspari, Oliver D. (Frontiers in Plant Science, 2022)
The N-terminal sequence stretch that defines subcellular targeting for most nuclear encoded chloroplast proteins is usually considered identical to the sequence that is cleaved upon import. Yet here this study shows that for eight out of ten tested Chlamydomonas chloroplast transit peptides, significant additional sequence stretches past the cleavage site are required to enable efficient chloroplast import of heterologous cargo proteins. Analysis of Chlamydomonas cTPs with known cleavage sites and replacements of native post-cleavage residues with alternative sequences points to a role for unstructured sequence at mature protein N-termini.